1976
DOI: 10.1021/j100553a017
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric properties of Rhodamine B in glycerol, ethylene glycol, and acetic acid

Abstract: Publication costs assisted by Keio University Absorption spectra of rhodamine B are examined in solutions of glycerol, ethylene glycol, and acetic acid. Particular attention is given to the absorption spectra of monomers and dimers of rhodamine B in these solutions. Furthermore, dimeric structures of rhodamine B in these solutions are also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…In order to investigate the photocatalytic activity of the ZnSe nanoparticles, RhB is chosen as the photocatalytic degradation dye since it is a good model compound as a target pollutant that is stable under UV irradiation [36]. Prior to the photocatalytic reaction, the RhB solutions are first photolyzed in the absence of the photocatalysts to determine their stability.…”
Section: àmentioning
confidence: 99%
“…In order to investigate the photocatalytic activity of the ZnSe nanoparticles, RhB is chosen as the photocatalytic degradation dye since it is a good model compound as a target pollutant that is stable under UV irradiation [36]. Prior to the photocatalytic reaction, the RhB solutions are first photolyzed in the absence of the photocatalysts to determine their stability.…”
Section: àmentioning
confidence: 99%
“…It is well known that dye molecules tend to form supramolecular architectures via self-assembly in solution or in adsorbed states [8][9][10][11][12][13][14][15]. For example, Tian et al [3,16] fabricated lowdimensional nanorods and nanospheres of a stilbazolium-like organic dye with highly monodisperse size using a self-assembly method.…”
Section: Introductionmentioning
confidence: 99%
“…This form is stabilized in the presence of polar protic or chlorinated solvents such as those used in the present synthesis, whereas the colorless (λ max abs = 316 nm) and weakly fluorescent lactone form (Scheme S2, Supporting Information) is generally stabilized in nonpolar solvents (e.g., cyclohexane) . Worth to mention though, the Vis absorption band at (λ max = 557 nm) is shifted by comparison with the one obtained for a bulk solution measurement (λ max abs = 545 nm) pointing out already to solvatochromism and the formation of aggregates within the nanoparticles. This aggregation was confirmed by fluorescence spectra (Figure b), which exhibits a very weak and broad band at λ max = 610 nm (≈40 nm red‐shifted with respect to the corresponding measurement in an organic solution).…”
Section: Resultsmentioning
confidence: 64%
“…The pink and highly fluorescent (λ max emi = 595 nm) solution obtained by dissolving the RhB‐base in liquid DA ( T > T m DA , 47 × 10 −6 m ) was in agreement with the formation mostly of the RhB‐zw form (Figure S5, Supporting Information). The lack of any fluorescence enhancement upon addition of glacial acetic acid (Figure S6, Supporting Information), which is described to boost the formation of the RhB‐zw form,[20,21a] confirmed that the formation of this species was almost quantitative already in liquid DA. At lower temperatures ( T < T m DA ), the solution solidified while maintaining the pink color characteristic of the RhB‐zw form.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation